Efeitos ecotoxicológicos das nanopartículas de dióxido de titânio sobre a alga Pseudokirchneriella Subcapitata e sobre o Cladócero Ceriodaphnia Silvestrii por diferentes vias de exposição - Lucca, Gisele Maria de (Universidade Federal de São Carlos, 2016)
In recent years, increased use of titanium dioxide nanoparticles (TiO 2 NPs) in consumer products and technological devices has raised concerns regarding their environmental impacts and their risks to human health. Ecotoxicological studies have been used as a tool to analyze the toxic potential of TiO 2 NP S in different trophic levels, such as primary producers (algae) and first order consumers (cladocerans). In the present study, the chronic effects of TiO2 NPS on the population growth of the microalgae chlorophycean Pseudokirchneriella subcapitata was evaluated during an exposure period of 96 hours, under conditions of temperature and photoperiod similar to those found in tropical ecosystems. New methods were developed for the separation of the aggregates between the algae cells and TiO2 NPS, whose formation was observed at above 0.01 mg L-1 concentrations after a period of 96 hours’ exposure. The only effective method was the one in which the cells were washed three times with a metal chelator (EDTA), with duration of 1 minute for each wash. In the toxicity chronic test, there was obtained a significant inhibition of algal growth from the concentration of 64 mg L-1 of TiO2 NPs, with a concentration of 50% inhibition of algal cells (96 h - IC50) of 201.22 mg L -1 in 96 h of exposure. Then, it was evaluated the acute effects of exposure by contact and the chronic effects of TiO2 NPs for the cladoceran Ceriodaphnia silvestrii, using contaminated food (Pseudokirchneriella subcapitata) as a route of exposure. In acute toxicity tests was obtained the average value of EC50 - 48 h of 77.57 mg L-1. In chronic toxicity tests, it was observed significant differences in survival from the concentration of 0.01 mg L-1, while for the body length, the number of eggs and neonates produced, toxic effects were observed from the concentration of 1 mg L-1. These results indicate that the nano-TiO2 NPS had a deleterious effect on the growth of Pseudokirchneriella subcapitata only at concentrations above those normally found in natural aquatic environments. For the cladoceran Ceriodaphnia silvestrii, the route of dietary exposure indicated a greater toxic effect.
Ecotoxicological effects of the titanium dioxide nanoparticles on the algae Pseudokirchneriella subcapitata and on the cladoceran Ceriodaphnia silvestrii by different exposure routes
Keywords: Ecotoxicologia; Método de desagregação; Nano-tio2; Microalga; Cladócero; Ecotoxicology; Method of disaggregation; Dietary; Microalgae; Cladoceran; TiO2 NPS; CIENCIAS BIOLOGICAS